"We Are The World Itself": The Construction Of "Good" Citizenship And Deviations From It In Ergo Proxy - Dasgupta, Arnab (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Anime is the dominant medium of pop-culture expression in modern Japan, lending itself readily to genres such as romance and comedy, as well as advanced concepts of social and political discourse. At the same time, the rise of modern anime, especially science fction anime coincided with the coming to the forefront of the issue of immigration. This article attempts to understand how the two phenomena may be intertwined in the dialectical process of analysing and re-analysing national identity and belonging, through a critical interpretation of the anime series Ergo Proxy, released in 2006. The ideas outlined below are relevant both to critical discourse studies and for prospective solutions in the feld of immigration policy. With Japan's economy going into a tailspin due to the explosion of the housing bubble in the 1990s, coupled with the detrimental eﬀects of negative population growth, more and more industries found themselves reliant on immigrant labour for their survival, even as national political winds blew decisively against opening the country to immigrants, due to unforeseen eﬀects on "the Japanese way of life." As Japan entered the second decade of its persistent recessionary state, and the government remained impassive to calls issued from several quarters of society to liberalise immigration policy, even though many of these workers were urgently required in such important sectors as construction and healthcare, clinging instead to outdated racist notions of "pure Japaneseness," a trickle of foreign workers continued to enter Japan, becoming subject to abuse and human rights violations as their existence continues to be systematically erased.